Self-Inflicted Orbito-Cranial Injury Secondary to Gunshot: Case Report - Roka, Yam Bahadur; Bhattarai, Narayani Roka (Journal of College of Medical Sciences-Nepal, 2017)
The eye may be injured by various penetrating and non-penetrating injuries like sticks, pencils, rods, gunshot and chopsticks. Self-inflicted gunshot injuries have been rarely reported in literature. This case is interesting in multiple aspects which include poverty, lack of education and the failure of government to ensure control of the use of firearms in Nepal. We report a case of self-inflicted gun injury which was managed successfully.